2013
DOI: 10.14712/18059694.2014.18
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Arthroplasty in Patients With Parkinson's Disease

Abstract: The aim of this study is to evaluate the results of total hip arthroplasty in patients with Parkinson's disease during a period of five years, focusing on the assessment of the risks and benefits of surgery. During this period we performed total hip arthroplasty in 14 patients (15 hips) with Parkinson's disease. Patients were evaluated by subjective symptoms and objective findings, with a focus on the use of support while walking and walking distance, severity of Parkinson's disease before surgery and at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
4
20
1
Order By: Relevance
“…THA in patients with PD is a challenging surgery because of associated comorbidity and complications. Previous studies reported the high general and local complication rates in these patients (2,4). Our results indicate that 11 patients with primary THA (29.7%) and 8 patients with revision THA (40.0%) had general complications, consistent with previously published works.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…THA in patients with PD is a challenging surgery because of associated comorbidity and complications. Previous studies reported the high general and local complication rates in these patients (2,4). Our results indicate that 11 patients with primary THA (29.7%) and 8 patients with revision THA (40.0%) had general complications, consistent with previously published works.…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports of the outcome of THA in PD patients indicate that acetabular and femoral component fixation in THA can be achieved using cemented devices [2,4,6]. A recent meta-analysis concluded that PD patients were at higher risk of osteoporosis than healthy control subjects (OR 2.61) [34].…”
Section: Stagementioning
confidence: 99%
See 1 more Smart Citation
“…These findings are corroborated by previous reports of high rates of infections (i.e., superficial wound infections, urinary tract infections) and psychoses following surgery among THA patients with neurodegenerative disease or a history of substance abuse, respectively. 2830 …”
Section: Discussionmentioning
confidence: 99%
“…35 Patients with Parkinson’s disease experience much higher complication rates (26% – 68%) and 6-month mortality rates (5.6% – 21%) after primary THA than those patients without Parkinson’s disease. 28,30 Mental disability has been associated with longer LOS, greater inpatient costs, and higher rates of complications. 36 Revision arthroplasty is a clinically complex endeavor often resulting in net institutional financial losses.…”
Section: Discussionmentioning
confidence: 99%